Resilience of the Economic and Monetary Union – The Contribution of Fiscal Consolidation and Public Debt in the European Union - Catarino, Ricardo; Nunes, Alexandre; Borrego, Pedro; Sobral, SUsana; Ferraz, David (Conference of the International Institute of Administrative Science (IIAS), 2025)
The success of economic and monetary integration within the European Union relies on the careful management of budget deficits and public debt levels among member states to ensure strong financial sustainability and resilience to achieve a greater capacity to address crises. Conversely, high public debt levels often persist and adversely affect long-term economic growth (Kumar & Woo, 2015; Reinhart et al., 2012). Countries with persistently high public debt risk elevate financial markets’ perception of unsustainability in their public finances (IMF, 2023; Mateus, 2018; Romano, 2017). The IMF (2023) has observed a notably negative trend in global public debt levels, which reached record highs in 2024, and argues that the risks associated with elevated sovereign debt levels necessitate a globally coordinated approach to managing excess debt, especially for more vulnerable states. The IMF also notes that this negative trend will vary significantly across different world regions. For example, estimates for the 27 EU member states suggest notable consolidation (improvement) in public debt levels is expected. However, the EU’s 27 member states do not all face identical obligations regarding budgetary consolidation: while 20 have adopted the single currency, seven have not. This quantitative and qualitative study examines the evolution of public debt and budget deficits across the EU’s 27 member states between 2018 and 2023, examining the behaviour of different member states during this period. The selected time is significant for understanding the evolution of public debt and budget deficits and the effects of the temporary suspension, from 2021 to the end of 2023, of the SGP’s deficit and debt limits for member states. We aim to characterise and compare the financial behaviour of eurozone and non-eurozone members. The data collected from Eurostat databases indicate that long-term consolidation and sustainability and resilience are structurally incorporated into the national finance management of both groups of states. Furthermore, we conclude that increased autonomy for member states has not led to a disregard of fiscal rules, nor a neglect of the risks that high deficits and debt levels pose to the resilience of EU member states in potential future crises.